LncRNA MALAT1 Suppression Protects Endothelium against oxLDL-Induced Inflammation via Inhibiting Expression of MiR-181b Target Gene TOX. (16th December 2019) - Wang, Liuqing; Qi, Yinliang; Wang, Yi; Tang, Haitao; Li, Zhenzhen; Wang, Yuan; Tang, Songtao; Zhu, Huaqing
Abstract : Rare studies have been conducted to investigate the exact interactions between lung adenocarcinoma transcript 1 (MALAT1), thymocyte selection-associated high mobility group box (TOX), and miRNAs in the pathogenesis of atherosclerosis (AS). We aim to investigate the crosstalk between MALAT1 and TOX and evaluate whether the regulatory mechanism was associated with the miRNA network. AS tissues were collected to determine the level of MALAT1 expression in AS patients, together with determination of miR-181b expression. Cultured endothelial cells were utilized to analyze the expressions of MALAT1, miR-181b, and TOX in the presence of oxLDL. Luciferase activity assay was conducted to evaluate the potential target sites of miR-181b on MALAT1 and TOX. In this study, we demonstrated that MALAT1 was upregulated in patients with AS. MALAT1 silencing significantly downregulated the expression of the miR-181b target gene TOX via reversing the effect of miR181b. Importantly, positive modulation of miR181b and inhibition of MALAT1 and TOX significantly attenuated oxLDL-induced endothelial inflammation and oxidative stress. Moreover, the MAPK signal pathways in endothelial cells were also inhibited through regulation of above endogenous RNAs. In summary, MALAT1 suppression protects the endothelium from oxLDL-induced inflammation and oxidative stress in endothelial cells by upregulation of miR-181b and downregulation of TOX.